TRADITIONAL INK PAINTING'S CONTEMPORARY EXPRESSION: STUDY ON THE ARTISTIC LANGUAGE, AESTHETIC ORIENTATION, AND DEVELOPMENT STRATEGIES OF CHINESE NEW INK PAINTERS - Shan, Wan; Somtai, Pitiwat (Asia Pacific Journal of Religions and Cultures, 2025)
Chinese traditional ink painting, as an important art form, has developed over thousands of years, carrying rich cultural connotations and philosophical thoughts. However, with the globalization and modernization processes accelerating in the late 20th century, traditional ink painting faces challenges and impacts from Western modern art. To adapt to contemporary societal aesthetic demands and cultural changes, many Chinese artists have integrated modern artistic concepts into traditional techniques, giving rise to the "New Ink" art trend, which promotes innovation and development in ink painting. This study employs literature review, case analysis, and interdisciplinary research methods to analyze the artistic language of Chinese new ink painters and their modern expressions, as well as to explore how their aesthetic orientations respond to contemporary cultural needs and aesthetic trends. The research findings indicate that new ink painters, while inheriting the core techniques of traditional ink painting, have developed a unique modern artistic language by introducing non-traditional materials, innovating expressive forms, and enriching thematic content. Furthermore, the study reveals various challenges faced by new ink painters in their artistic creation and proposes strategies for the protection and promotion of this art form's sustainable development through educational transmission, market promotion, and cultural policy support.